Safety of a pacemaker mode intended to protect patients - Robert G. Hauser, MD, FHRS; Melanie Kapphahn-Bergs, RN, CCDS; Ali Bahbah, MD; Dawn Witt, PhD, MPH; Larissa I. Stanberry, PhD; Jay D. Sengupta, MD, FHRS (Heart Rhythm O2)
Background: In 2021, Boston Scientific (BSC) announced that its Ingenio pacemakers (PMs) could exhibit high internal battery impedances (HIBIs) and trigger the safety mode (SM) that should preserve pacing when PM function is jeopardized. SM is VVI or biventricular pacing, 72.5 bpm, and unipolar, with a sensitivity of 0.25 mV. In 2023, BSC said SM may pause pacing and 3 deaths occurred in PM-dependent patients. In 2024, BSC warned that some Accolade PMs had HIBI and SM could occur. Objective: This study aimed to quantify adverse events (AEs) associated with SM and compare them with Abbott’s backup (BU), Medtronic’s reset (RE), and Biotronik’s backup mode. Methods: The Food and Drug Administration’s Manufacturer and User Facility Device Experience database was searched from 2021 to 2024 for AE involving SM, BU, RE, and backup mode. Results: We found 1379 AEs, including 13 deaths and 574 major AEs; 525 AEs (91.5%) were PMs in SM vs 31 (5.4%) in BU, 18 (3.1%) in RE, and none (P < .001) in backup mode. SM was associated with 349 syncopal events that resulted in head injuries (n = 25) or falls (n = 20); BU- or RE-related syncopal events resulted in 1 head injury and no falls (P < .001). Pacing inhibition was described for 204 SM-related syncopal events (58.%) but none for BU or RE. HIBI was the most common but not an exclusive cause of SM. Conclusion: SM is associated with major AEs that are more numerous and serious than BU, RE, or backup mode. Most SM AEs seem related to its high sensitivity (0.25 mV), and consequently, SM may be unsafe for PM-dependent patients.